The neurological consequences of contracting COVID-19 - Aknin, LB; De Neve, JE; Dunn, EW; Fancourt, DE; Goldberg, E; Helliwell, JF; Jones, SP; Karam, E; Layard, R; Lyubomirsky, S; Rzepa, A; Saxena, S; et al. (MedSport Press, 2021)
Since the first confirmed case in Wuhan, China on December 31, 2019, the novel coronavirus (SARS-CoV-2) has spread quickly, infecting 165 million people as of May 2021. Since this first detection, research has indicated that people contracting the virus may suffer neurological and mental disorders and deficits, in addition to the respiratory and other organ challenges caused by COVID-19. Specifically, early evidence suggests that COVID-19 has both mild (e.g., loss of smell (anosmia), loss of taste (ageusia), latent blinks (heterophila), headaches, dizziness, confusion) and more severe outcomes (e.g., cognitive impairments, seizures, delirium, psychosis, strokes). Longer-term neurological challenges or damage may also occur. This knowledge should inform clinical guidelines, assessment, and public health planning while more systematic research using biological, clinical, and longitudinal methods provides further insights.